The Opportunity Costs of Public Investment: Comment - Diamond, Peter (Quarterly Journal of Economics, 1968)
Journal Article The Opportunity Costs of Public Investment: Comment Get access Peter Diamond Peter Diamond Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 4, November 1968, Pages 682–688, https://doi.org/10.2307/1879607 Published: 01 November 1968